Prevalence of Metabolic Syndrome and Associated Factors among Workers: The Case of Two Port Companies in Cotonou, Benin (2019) - HINSON, Antoine Vikkey; ADJOBIME, MENONLI; AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU (My University, 2021)
Background: Metabolic Syndrome (MetS) is developed by a combination of several risk factors, which can increase the likelihood of cardiovascular diseases and diabetes. The present study aimed to evaluate the prevalence of MetS and its associated factors among Cotonou Port workers. Materials and Methods: This cross-sectional study was conducted for descriptive and analytical purposes. The administration of the questionnaire was inspired by WHO STEPS, with biological examinations performed. MetS was selected according to the criteria of the International Diabetes Federation (IDF). The data were analyzed using R 3.6.1 software. Besides, a univariate analysis and a multivariate logistic regression analysis were performed to determine MetS-associated factors. Results: Our study population consisted of a total of 349 workers aged 23 to 64 years. Besides, the prevalence of MetS was 18.1%. The most common features of the workers were blood pressure ≥ 130/85 mmHg (92.1%) followed by abdominal obesity (76.3%) and glycemia ≥ 1 g/l (65.1%). After multivariate analysis, factors associated with MetS included age > 50 years (ORa = 3.97 CI95% [1.71 – 9.36], p=0.006), alcoholism (ORa = 2.05; CI95% [1.07 - 4.15], p=0.031), family history of hypertension (ORa = 2.08; CI95% [1.11 - 4.01], p=0.022) , overweight (ORa = 4.87 CI95% [2.10 - 12.75], p=0.001) and obesity (ORa = 5.80 CI95% [2.42 - 15.59], p= 0.001). Conclusion: The MetS frequency is high among Cotonou Port workers. Accordingly, it is necessary to identify the related risks to take adequate preventive measures and to promote the workers' health.
Keywords: Metabolic Syndrome; Workplace; Benin